The Impact of Complex Preoperative Preparation of Patients with Aortic Heart Diseases on the Level of Postoperative Anemia - B. M. Gumeniuk; V. V. Popov; A. K. Logutov; E. V. Aksenov (Ukrainian Journal of Cardiovascular Surgery, 2020)
In patients undergoing surgical treatment of aortic heart defects under artificial circulation, pre-operative correction of serum iron levels, and application of blood-saving techniques during surgery reduce the level of postoperative anemia.The aim. To investigate the combined influence of preoperative correction of serum iron levels and blood-saving techniques in the early postoperative anemia in the surgical treatment of aortic heart defects under artificial circulation.Material and methods. This study involves 133 patients with acquired aortic heart diseases undergoing surgical treatment under artificial circulation and aims at identifying the combined effect of preoperative correction of serum iron (III) hydroxide levels and blood-saving techniques on the level of postoperative anemia. The levels of iron, transport enzymes, blood corpuscles, Hb and Ht were investigated. All the patients were divided into 3 groups. Group A (control group) included 52 patients in whom iron levels were within the normal range and donated blood components were used during the intervention. Group B (study group) included 43 patients in whom iron levels were within the normal range and blood-saving techniques were used during the intervention. Group C (adjustment group) included 38 patients with low iron levels and anemia, which was interpreted as anemia of chronic disease (ACD). Preoperative correction of serum iron levels and intraoperative blood-saving techniques were applied in this group.Results. For the purpose of perioperative anemia correction, transfusion of 539.8 ± 9.1 ml (p¤0.05) of packed red blood cells and 582.4 ± 77.2 ml (p¤0.05) of fresh frozen plasma was given in Group A patients. In the Group B, the use of blood-saving techniques during the intervention allowed us to obtain good clinical effect without perioperative transfusion of blood products. It was established that in Group C preoperative correction of serum iron enabled to achieve 5.6 times higher level of serum iron (p¤0.05), 2 times higher transferrin saturation, and 7.3 times higher ferritin activity (p¤0.05), as well as increase preoperative Hb level by 9.5 % and decrease postoperative anemia by 8.7 %.Conclusions. Correction of low baseline serum iron in patients with chronic anemia (ACD) provides 5.6 times increase in preoperative serum iron (SI) (p¤0.05), increases hemoglobin by 9.5% (p¤0.05), and reduces the level of postoperative anemia in patients undergoing surgical treatment of aortic heart defects under artificial circulation with the use of blood-saving techniques and without the use of donor blood and Cell Saver.